KEBERADAAN ESCHERICHIA COLI DAN HIGIENE SANITASI DEPOT AIR MINUM (DAMIU) DI WILAYAH KECAMATAN CIAMIS - sari, Gira Intan; Saraswati, Dian; Setiyono, Andik (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2025)
Sanitation and hygiene regulations in handling drinking water must be adhered to during the processing, packaging and serving of processed drinking water at refill drinking water depots (DAMIU). Protected water must be free from microbiological, chemical, and physical contaminants. The purpose of this study was to determine the presence of Escherichia coli bacteria in refill drinking water at drinking water depots in the Ciamis Regency Region, as well as to determine the sanitary hygiene of drinking water depots which includes aspects of place sanitation, equipment sanitation, handler hygiene, raw water, and drinking water. This study combines Descriptive Observational with Cross Sectional design. Site sanitation, equipment sanitation, handler hygiene, raw water and drinking water quality, and the presence of Escherichia coli are some of the variables in this study. The results of this study from 29 refill drinking water depots, there are some that do not meet sanitary hygiene standards, such as being near pollutant sources such as workshops and roadsides;, some still have problems with lighting and ventilation, some of them do not have hand washing stations, handlers do not wash their hands before refilling gallons of water or afterwards, handlers do not follow sanitary hygiene practices such as smoking, handlers do not have sanitary hygiene training certificates, and they do not have routine health checks at least twice a year. The conclusion of this study is that out of 29 drinking water depots, there are 6 that comply with the sanitary hygiene requirements of drinking water depots and in the quality of drinking water there are 6 depots that do not comply with drinking water quality requirements (Escherichia coli is present).